The Role of The Holy Spirit in Acts 1:8 - Woy, Jones Ted Lauda (Klabat Theological Review, 2025)
This research explores the significance of the Holy Spirit in Acts 1:8, emphasizing Luke’s theological portrayal of the Spirit as the source of power for the early Christian witness. Through a detailed examination of the Acts narrative and engagement with scholarly perspectives, the study underscores the Holy Spirit’s essential role in equipping the disciples for gospel proclamation. The analysis centers on two key theological inquiries: (1) How does Luke define the identity of the Holy Spirit? and (2) What function does the Spirit fulfill within the early Church? Utilizing the historical-grammatical method of interpretation, the study draws on scriptural texts and academic resources. The research aims to contribute to a deeper theological understanding among pastors, church leaders, and congregants regarding the Holy Spirit’s role in the mission of the early Church as depicted in the New Testament. Keywords: Holy Spirit, Equipping, Witness, Ministry, and Mission.